Saliva’s Biochemical Analysis for The Diagnosis of Systemic and Oral Diseases: A Review - Oudah, Shamam; Nsaif Ali, Izdihar; Hanan, Zaman (Journal of Biomedicine and Biochemistry, 2024)
Background The diagnostic use of saliva for systemic and oral disor- ders is reviewed in this article. Saliva has unique advantages over serum as a diagnostic fluid because it is non-invasive and can be obtained by anyone with a little training. Saliva may also provide a financially reasonable way to screen large populations. Saliva from a single large salivary gland can be used to diagnose diseases unique to that gland. However, because whole saliva is easy to obtain and contains serum components, it is commonly used to diagnose oral and systemic disorders. However, saliva contains a more diverse microbial habitat and a lower concentration of biomolecules compared to blood, which may have an unexpected impact on the detection results.Purpose These issues will eventually be solved by creating and develop- ing a highly sensitive detection platform, and saliva testing will likely open new horizons for saliva detection. Identify the disease . Researchers use a variety of techniques and techniques in an attempt to identify salivary biomarkers for systemic and oral disorders inLast few years. The review aspires to provide a comprehensive perspective on salivary biomarkers in relation to oral and systemic diseases. Saliva analysis may be useful in di- agnosing genetic disorders, autoimmune diseases, malignant and infectious diseases, and endocrine disorders, as well as in assessing therapeutic levels of drugs and monitoring illicit drug use.Conclusion The various tasks that saliva completes in the oral cavity are accomplished by the biochemical, physical, and interaction character- istics of these salivary constituents. These days, there are numerous assays available to examine different salivary parameters; nevertheless, in order to get significant data, collection and storage procedures must be standard- ized.